Exploration of utility of combined optical photothermal infrared and Raman imaging for investigating the chemical composition of microcalcifications in breast cancer. Issue 13 (7th March 2023) - Bouzy, Pascaline; Lyburn, Iain D.; Pinder, Sarah E.; Scott, Robert; Mansfield, Jessica; Moger, Julian; Greenwood, Charlene; Bouybayoune, Ihssane; Cornford, Eleanor; Rogers, Keith; Stone, Nick
Abstract : We aim to develop a protocol for efficiently analysing breast microcalcifications and their microenvironment in detail by combining O-PTIR and Raman spectroscopy at the same time, the same location and the same high resolution (0.5 μm). Abstract : Microcalcifications play an important role in cancer detection. They are evaluated by their radiological and histological characteristics but it is challenging to find a link between their morphology, their composition and the nature of a specific type of breast lesion. Whilst there are some mammographic features that are either typically benign or typically malignant often the appearances are indeterminate. Here, we explore a large range of vibrational spectroscopic and multiphoton imaging techniques in order to gain more information about the composition of the microcalcifications. For the first time, we validated the presence of carbonate ions in the microcalcifications by O-PTIR and Raman spectroscopy at the same time, the same location and the same high resolution (0.5 μm). Furthermore, the use of multiphoton imaging allowed us to create stimulated Raman histology (SRH) images which mimic histological images with all chemical information. In conclusion, we established a protocol for efficiently analysing the microcalcifications by iteratively refining the area of interest.